A Variety of Entrepreneurial Motives: GEM Slovenia 2019, Executive Summary (University of Maribor Press, 2020)
In the world’s largest longitudinal survey, the Global Entrepreneurship Monitor (GEM), we have been exploring important features of entrepreneurship for 21 years, with particular emphasis on the earliest stages when business opportunities are perceived and individuals decide whether to engage in entrepreneurship. GEM was designed to (1) measure differences in attitudes towards entrepreneurship, activities and aspirations of individuals in as many countries as possible, (2) identify factors that encourage or hinder entrepreneurial activity, especially in relation to societal values, personal characteristics and the entrepreneurial ecosystem, (3) provide a platform for assessing the impact of entrepreneurial activity on economic growth in a given economy, and (4) identify the necessary policy measures to strengthen entrepreneurship. With the help of this research, we better understand society’s attitude towards entrepreneurship and characteristics of the individual, such as perception of one’s own abilities for entrepreneurial activity, ability to perceive opportunities, entrepreneurial intentions, and fear of failure. As GEM monitors entrepreneurial activity throughout the phases of the life cycle (nascent, new businesses and established businesses, discontinuation), according to impact (high growth, innovation, internationalization) and by type (early-stage entrepreneurship activity, employee entrepreneurship activity), the picture is much richer than the one that is based only on data gathered from ordinary statistical databases.